Analisis Pengaruh Kepemimpinan Autentik dan Budaya Organisasi terhadap Kinerja dengan Kepuasan Karyawan sebagai Mediator: Studi Kasus Satoria Pharma - Christina , Enge; Tjahjadi , Bambang; Choirunnisa , Zuyyinna (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of authentic leadership and organizational culture on employee performance, with employee satisfaction as a mediating variable at Satoria Pharma. Using an explanatory quantitative design, data were collected from 75 employees through questionnaires and analyzed using regression, path analysis, and the Sobel test. The results show that authentic leadership and organizational culture significantly affect employee satisfaction and performance. However, employee satisfaction does not significantly influence performance and fails to mediate the relationships. These findings imply that in highly regulated industries, performance is driven more by direct leadership and cultural alignment than by employee satisfaction. Keywords: Authentic Leadership, Organizational Culture, Employee Satisfaction, Employee Performance, Pharmaceutical Industry, Mediation Effect, Organizational Behavior